The Use Of "Powle" Media as An Effort to Increase Learning Motivation, Interest and Talent of Children At SDN 3 Sukajaya - Nuraeni, Fitri; Nurfadillah, Andriana; Sephi, Yayu; Rahayu, Santi Nurhaliza; Silhubah, Rifa; Zaviani, Ilma Suci; Iqbal, Muahmmad; Lestaluhu, Ledi; Rosyad, Muhammad Fauzi; Fauziyah, Anisa Nur; Aulia, Lutfi; Siami, Novita; Suhati, Teti; Makiyah, Dinar; Istidadah, Feida Noorlaila (AbdimasMu UMTAS, 2025)
Education is a conscious and planned effort that can be done by everyone to gain knowledge and experience that can be used for the progress of the individual himself, as well as the local community. Education is one of the mandatory things to do to improve the quality of Human Resources (HR) in Sukajaya Village, especially at SDN 3 Sukajaya. The implementation of this community service activity was carried out on August 8 - September 8, 2022 at Babakanjaya Village, Sukajaya Village, Cimerak District, Pangandaran Regency. This community service activity aims to increase students' learning motivation, interests and talents so that they can maintain a mindset on the importance of education so that there are no more problems with children dropping out of school in Sukajaya Village. The provision of learning motivation is carried out using the puppet dream media with the storytelling method in which the story is made by the child himself related to the ideals and motivation of the child to achieve a dream. The results of this activity are in the form of a dream stage which makes a stage for the 5th and 6th grade students of SDN 3 Sukajaya where students can display their own work in front of the class by demonstrating the dream puppet and be able to tell what they aspire to. In addition, education and health seminar activities are also the final result of KKN students with the aim of targeting students' parents and teachers at SDN 3 Sukajaya. With hope that parents and teacher can further increase the motivation, interest and talents of students in the field of education from the program that has been implemented